
∵△y=1/√(x+△x)-1/√x=√x-√(x+△x)/√(x^2+x·△x)=-△x/【√(x^2+x·△x)(√x+√x+△x)
∵△y=1/√(x+△x)-1/√x=√x-√(x+△x)/√(x^2+x·△x)=-△x/【√(x^2+x·△x)(√x+√x+△x)】∴△y/△x=-1/【√(x^2...
∵△y=1/√(x+△x)-1/√x=√x-√(x+△x)/√(x^2+x·△x)=-△x/【√(x^2+x·△x)(√x+√x+△x)】∴△y/△x=-1/【√(x^2+x·△x)(√x+√x+△x)】∴lim△x→0△y/△x=-1/(2x√x)=-1/2x^-3/2
1/【√(x^2+x·△x)(√x+√x+△x)怎么转换成m△x→0△y/△x=-1/(2x√x)=-1/2x^-3/2 展开
1/【√(x^2+x·△x)(√x+√x+△x)怎么转换成m△x→0△y/△x=-1/(2x√x)=-1/2x^-3/2 展开
2个回答
展开全部
△x→0
所以把△x看成0
所以1/【√(x^2+x·△x)(√x+√x+△x)
=1/[√x^2*(√x+√x)]
=1/(2x√x)
所以把△x看成0
所以1/【√(x^2+x·△x)(√x+√x+△x)
=1/[√x^2*(√x+√x)]
=1/(2x√x)
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询